Diversity of insect pests of okra under red lateritic zone of West Bengal (The Journal of Plant Protection Sciences, 2023)
Okra, Abelmoschus esculentus (L) Moench  belonging to the family Malvaceae, is a popu lar and commercially cultivated vegetable crop of tropical and subtropical parts of the world. India ranked first in okra production in the World and major okra producing Indian states are Uttar Pradesh, Bihar, Orissa, West Bengal, Andhra Pradesh, Karnataka and As sam (1). Okra fruit is very rich in fats, carbo hydrates, vitamins like A & B vitamins and  minerals such as calcium, iron, magnesium and potassium (2). Apart from these, the fruit  is very useful against genito-urinary disor ders, spermatorrhoea and chronic dysentery  (7).
Keywords: infestations; vitamins; Rathindra Krishi Vigyan Kendra